Optimalisasi Kinerja Pegawai Non PNS di Balai Prasarana Permukiman Wilayah Gorontalo - Fitriani Karim, Dian; Suprapto, Sri handayani; Kurniati Mohi, Widya (CV. Publikasi Indonesia, 2023)
This study aims to determine the optimization of the performance of non-civil servants at the Gorontalo Regional Settlement Infrastructure Center. The research method uses a qualitative type. The results showed that the performance of non-civil servants at the Gorontalo Regional Residential Infrastructure Center was not fully optimal. This is shown from the aspect of the quantity of work of non-civil servant employees at the Gorontalo Regional Settlement Infrastructure not optimal. This can be seen from the many work that has not been completed by non-civil servants at the Gorontalo Regional Settlement Infrastructure Center until the specified time limit. From the aspect of the quality of work for non-civil servant employees, the Gorontalo Regional Settlement Infrastructure Center has not been optimal. This can be seen from the many non-civil servants who do not understand their work and the results of the work are not in accordance with the results expected by the agency. From the aspect of timeliness of work for non-civil servants, the Gorontalo Regional Settlement Infrastructure Center has not been optimal. This can be seen from the many non-civil servants who do not comply with the predetermined office hours and have an impact on delays in work reports.